PRODUKSI SENYAWA BAKTERIOSIN SECARA FERMENTASI MENGGUNAKAN ISOLAT BAL Enterococcus faecium DU55 DARI DANGKE - Abd. Rahman Razak; Abd. Rauf patong; Tjodi Harlim; M. Natsir Djide; Haslia Haslia; Mahdalia Mahdalia (Hasanuddin University, 2009)
Dangke is one of traditional food from Enrekang Province Sulawesi Selatan which is made from buffalo milk and enzimatically processed using papain from papaya’s gland secretion. Research on this local product as source of lactic acid bacteria (LAB) has been done. Counted 30 LAB was successfully isolated and 3 of them were potentially to be able to yield antimicrobial compound. Enterococcus faecium DU55 is one of LAB isolate available to be applied for producing bacteriocin compound through fermentation. Optimum condition of fermentation was specified by determining the highest antimicrobial activity generated by filtrate of fermentation result. Antimicrobial activity examination was carried out through diffusion agar method by measuring inhibition zone growth of pathogen bacterium Salmonella typhimurium FNCC 0050. Research results indicate that maximum bacteriocin compound production by BAL isolate E. faecium DU55 was obtained at condition of optimum fermentation at 30 °C during 42 hour using M1 medium with the same composition to medium MRS (Man Rogosa and Sharpe).Keyword: dangke, LAB isolate, bacteriocin, antimicrobial activity